1978
DOI: 10.1139/v78-058
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal reaction kinetics. The decomposition of nickel(II) hydroxide

Abstract: The fractional extent α of decomposition of ripened Ni(OH)2 into green NiO in alkaline hydrothermal conditions under nitrogen is given by the rate law α1/3 = kc[OH−]t, where kc = 2.4 × 10−5 kg mol−1 s−1 at 561 K. The Arrhenius activation energy is 220 + 25 kJ mol−1. The reaction is accelerated moderately by O2 (giving black NiO1+δ) and strongly by added NiO. A reaction mechanism involving dissolution of Ni(OH)2 as Ni(OH)3− (aq) and rate-determining, surface-controlled reprecipitation of this as NiO is proposed. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1978
1978
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…This activation is slightly higher (although perhaps not significantly) than most of the reported activation energies listed in Section 1 for isothermal decomposition. Perhaps more significantly, this study deduced that the nickel hydroxide decomposition obeyed first-order kinetics, not a contracting area/volume mechanism as other isothermal kinetic studies reported [19,21]. Sample size could certainly affect the observed mechanism.…”
Section: Isothermal-a Model Fitting (10 Mg Sample Mass)mentioning
confidence: 54%
See 2 more Smart Citations
“…This activation is slightly higher (although perhaps not significantly) than most of the reported activation energies listed in Section 1 for isothermal decomposition. Perhaps more significantly, this study deduced that the nickel hydroxide decomposition obeyed first-order kinetics, not a contracting area/volume mechanism as other isothermal kinetic studies reported [19,21]. Sample size could certainly affect the observed mechanism.…”
Section: Isothermal-a Model Fitting (10 Mg Sample Mass)mentioning
confidence: 54%
“…El-Salaam and Hassan [19] used a much larger sample size (500 mg) than our study (10 mg), so differing observed mechanisms would not be unexpected. However, Swaddle and Wong [21] used similar sized sample mass as this study, and still reported a contracting area/volume reaction model. The study by Swaddle and Wong did not appear to consider a great number of possible reaction mechanisms, nor did it perform any visual analysis or further study in an attempt to identify a mechanism, so perhaps a first-order decay fit their data equally well, but was not considered.…”
Section: Isothermal-a Model Fitting (10 Mg Sample Mass)mentioning
confidence: 99%
See 1 more Smart Citation
“…Ziemniak et al and Basavalingu et al, studied stability and thermodynamics of the CoO–H 2 O system under hydrothermal conditions and reported the P–T stability curve for the system. Swaddle et al studied hydrothermal decomposition of Ni­(OH) 2 in alkaline hydrothermal conditions under nitrogen, where NiO was the final product. Hazell et al studied hydrothermal decomposition and reported the kinetics to be much slower than that for vacuum, but quantitative kinetic data could not be obtained.…”
Section: Introductionmentioning
confidence: 99%
“…For Se, its concentration in the formation water increased by 11,800% (Table 3a). Adsorption of Se species onto the Fe, Mn, and Al-oxyhydroxides surfaces played an important role in Se concentrations in formation water (Swaddle and Wong, 1978). The extractable Fe and Mn extents in sandstone after reaction decreased, suggesting the contents of Fe and Mn-oxyhydroxides in sandstone decreased, resulting in the dissolution of the adsorbed selenium species into formation water (Table 3a).…”
Section: Dissolution Of Trace Elements In Sandstone and Shalementioning
confidence: 99%